1974
DOI: 10.1113/jphysiol.1974.sp010679
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine decarboxylase activity, nucleic acids and cell turnover in the livers of pregnant rats

Abstract: SUMMARY1. Comparisons were made between the livers of pregnant and nonpregnant rats, all of which were fed on a ration of 20 g food per day.2. In the second half of pregnancy there were marked increases in the weight of the liver and in its total content of protein, RNA and DNA. RNA concentration increased from the 15th day of gestation.3. Between the 12th and 18th day of pregnancy liver weight, total RNA, total DNA and mean liver cell nuclear volume increased in parallel at approximately the same rate of 6-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…The accelerated growth rate of the liver was maintained consistently over the whole period. Increases in the weight and protein content of the liver during pregnancy and lactation have been shown previously in rats (Chatwin et al, 1969;Campbell et al, 1974;Remesar et al, 1981;Mayel-Afshar & Grimble, 1982;Siebrits et al, 1985). The protein mass of the gastrointestinal tract also grew steadily throughout pregnancy and early lactation, but showed a particularly marked increase as lactation approached its peak at 15 days (Table 3).…”
Section: Rate Of Protein Synthesissupporting
confidence: 73%
“…The accelerated growth rate of the liver was maintained consistently over the whole period. Increases in the weight and protein content of the liver during pregnancy and lactation have been shown previously in rats (Chatwin et al, 1969;Campbell et al, 1974;Remesar et al, 1981;Mayel-Afshar & Grimble, 1982;Siebrits et al, 1985). The protein mass of the gastrointestinal tract also grew steadily throughout pregnancy and early lactation, but showed a particularly marked increase as lactation approached its peak at 15 days (Table 3).…”
Section: Rate Of Protein Synthesissupporting
confidence: 73%
“…Our observation that liver weight increases during pregnancy (Table 1) is consistent with that of other workers (2-4,23). The elevation in liver mass is generally attributed to the proliferation of parenchymal cells (24) and, indeed, we have observed that this enlargement is accompanied by an increase in total microsomal yield per liver. This is important when evaluating xenobiotic metabolism during pregnancy since this increase may represent a concomitant increase in the xenobiotic-metabolizing enzyme complements of the tissue.…”
Section: Discussionsupporting
confidence: 63%
“…Several workers have shown that livers of pregnant rats show a progressive increase in weight, RNA, DNA and protein during gestation (Morgan & Winick, 1977;Campbell, Fell & Mackie, 1974;Naismith, 1966). However, the present study has demonstrated that Fola te supp lernen ta tion and pregnancy the feeding of excess folate to rats during pregnancy is associated with an additional increment in hepatic growth.…”
Section: Discussionmentioning
confidence: 99%